EFFECT OF INJECTABLE COMBINATION ESTROGEN-PROGESTERON AND PROGESTERON-ONLY CONTRACEPTIVES ON GLUCOSE AND MALONDIALALDEHID SERUM - dwi retna prihati; Paryono Paryono; Wiwin Rohmawati (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2020)
Injectable hormonal contraception has been the most favorable contraception method in Indonesia in 2013 and its number reaches 4,128,115 acceptors (48.56%). The estrogen and progesterone contents in injectable contraception could cause stress, increased appetite, decreased leptin level and insulin resistance, eventually leading to increased blood glucose and serum malondialaldehyde levels. This study aims to observe the main effect of use of combined estrogen-progesteron and only progesteron injectable hormonal contraceptions on glucose level in blood and malondialaldehyde (MDA) level in serum. This is an experimental laboratory study. It uses Randomized pre-post test group research design for glucose level and randomized post test with control for malondialaldehyde level. The data are analyzed using Anova. The significance value is p<0.01. 28 samples are divided into 7 groups and each group consists of 4 samples, namely one control group and 6 treatment groups consisting of P1 combined dose 0.54 mg, P2 combined dose 1.08 mg, P3 combined dose 1.62 mg, P4 DMPA dose 2.7 mg, P5 DMPA dose 5.4 mg, P6 DMPA dose 8.1 mg. Only DMPA contraception at 0.54 mg dose influences the blood glucose level increase by p = 0.00. Only DMPA contraception at 8.1 mg dose does not influence serum MDA level by p = 0.1. The conclusion is DMPA contraception has greater potential of causing blood glucose level increase than the combined contraception. Combined and DMPA contraceptions share the risk of increasing serum MDA level.